Transient regulation of protein synthesis in Escherichia coli upon shift-up of growth temperature. - Yamamori, T (1978)
Synthesis of total cellular proteins of Escherichia coli was studied upon transfer of a log-phase culture from 30 (or 37) to 42 degrees C. Cells were pulse-labeled with [3H]leucine, and the labeled proteins were analyzed by gel electrophoresis in the presence of sodium dodecyl sulfate. The rates of synthesis of at least five protein chains were found to increase markedly (5- to 10-fold) within 5 min after temperature shift-up and gradually decrease to the new steady-state levels, in contrast to the majority of proteins which gradually increase to the steady-state levels (about 1.5-fold the rate at 30 degrees C). Temperature shift-down did not cause any appreciable changes in the pattern of protein synthesis as detected by the present method. Among the proteins greatly affected by the temperature shift-up were those with apparent molecular weights fo 87,000 (87K), 76K, 73K, 64K, and 61K. Two of them (64K and 61K) were found to be precipitated with specific antiserum against proteins that had previously been shown to have an adenosine triphosphatase activity. The bearings of these findings on bacterial adaptation to variation in growth temperature are discussed.